Mineral Preparation Using Rod Mill for Mineral Galena Characterization - Mirahati, Riria Zendy; Amalia, Yasmina; Juliyanto, Mochamad; Putri, Lintang Larasati Adi (RSF Conference Series: Engineering and Technology, 2022)
Galena mineral preparation was carried out for mineral characterization. The mineral characterization carried out included XRD (X-Ray Diffraction), XRF (X-Ray Fluorescence), SEM-EDS (Scanning Electron Microscope-Energy Dispersive X-Ray). The preparation of galena minerals begins with the process of reducing the grain size including crushing and grinding. The results of crushing and grinding are then separated based on grain size using a sieve or siever to get a grain size of -200 mesh. The grinding process using a rod mill needs to be timed, so that the results are not too fine which is causing the recovery in the mineral concentration process to be low.